Critical Points for the Organisation of Test Performance Studies in Microbiology Plant Pathogens as a Case Study - Vučurović, Ana; Mehle, Nataša; Anthoine, Géraldine; Dreo, Tanja; Ravnikar, Maja (Plant Pathology in the 21st Century, 2022)
This open access book in the field of plant pest detection shows a constant demand in development and improvement of fast and reliable detection tools, especially for high-priority pests. This open access book describes and summarizes the whole process of the organization of test performance study (TPS) for these tools. The outcome of TPS, obtained through the evaluation of the performance of one or more diagnostic tests by several laboratories on defined samples, is the finding of the best performing test/s for particular pest and for specific uses. Nowadays the intensification of worldwide trade and associated controls increases the need for quality assurance accreditation and harmonization of laboratories practices. Therefore, such studies are very important, but, non-existent. Considering those facts, our goal was to develop guidelines, by using the data and experiences of involved partners, for further TPS in the field of plant health. Developed guidelines could be easily transferable to other microbiology fields.